2012
DOI: 10.1007/s10236-012-0553-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved statistical prediction of surface currents based on historic HF-radar observations

Abstract: Accurate short-term prediction of surface currents can improve efficiency of search-and-rescue operations, oil-spill response, and marine operations. We developed a linear statistical model for predicting surface currents (up to 48 hours in the future) based on a short time-history of past HF-radar observations (past 48 hours) and an optional forecast of surface winds. Our model used empirical orthogonal functions (EOFs) to capture spatial correlations in the HF-radar data and used a linear autoregression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…The techniques applied include optimal interpolation (e.g., Breivik and Saetra, 2001), variational approaches (e.g., Sperrevik et al, 2015), and empirical methods without the use of a free model run (e.g., Wahle and Stanev, 2011;Frolov et al, 2012). Extensive validation of the performance of the HF radar data assimilation is provided by Barth et al (2008) using ADCP data, Yaremchuk et al (2016) using data from drifters, and Sperrevik et al (2015) using both drifters and ADCP data.…”
Section: The Variables Of Interest For Coastal Applications Includementioning
confidence: 99%
“…The techniques applied include optimal interpolation (e.g., Breivik and Saetra, 2001), variational approaches (e.g., Sperrevik et al, 2015), and empirical methods without the use of a free model run (e.g., Wahle and Stanev, 2011;Frolov et al, 2012). Extensive validation of the performance of the HF radar data assimilation is provided by Barth et al (2008) using ADCP data, Yaremchuk et al (2016) using data from drifters, and Sperrevik et al (2015) using both drifters and ADCP data.…”
Section: The Variables Of Interest For Coastal Applications Includementioning
confidence: 99%
“…In addition to a lot of scientific work related to the study and characterization of physical ocean processes, there are several other applications of HFR in research and marine management. Some of the examples provided in Paduan and Washburn (2013) include direct applications of HFR data to search and rescue (SAR) (Ullman et al, 2006) or oil-spill mitigation (e.g., Abascal et al, 2009;Frolov et al, 2012), marine traffic information (Breivik and Saetra, 2001), water quality assessment (e.g., Kim et al, 2009) and biological oceanography (e.g., Nishimoto and Washburn, 2002;Brzezinski and Washburn, 2011).…”
Section: Applications Of Hfr Measurements In the Framework Of The Eurmentioning
confidence: 99%
“…Orfila et al (2015) used a Genetic Algorithm to identify mathematical expressions that best forecast the time series of statistically significant EOFs. Solabarrieta et al (2016) applied the linear autoregressive models described in Frolov et al (2012) to perform an analysis of their spatio-temporal performances in a multi-year experiment in the Southeastern Bay of Biscay. A neural network based approach to obtain short term forecasts for currents and water levels from HFR data was presented in Wahle and Stanev (2011).…”
Section: Applications Of Hfr Measurements In the Framework Of The Eurmentioning
confidence: 99%
See 1 more Smart Citation
“…Karimi et al [35] found that ANN and ANFIS models gave similar forecasts and outperformed auto-regression moving average models (ARMA) for all the prediction intervals. Frolov et al [36] developed a statistical model for predicting surface currents based on historical HFR observations and forecasted winds. Frolov et al [36] found that the minimal length of the HF-radar data required to train an accurate statistical model was between one and two years, depending on the accuracy desired.…”
Section: Introductionmentioning
confidence: 99%